Proyecto de factibilidad para la creación de una empresa para comercializar e instalar alfombras residenciales, para el cantón Ibarra, provincia de Imbabura - Urbina, Gilber Miguel (2015)
The overall objective of this research is "Conduct a Feasibility Project for the Creation of a company to market and install Carpets Residential for Canton Ibarra, Imbabura Province in order to establish the return on investment"For the preparation of this research and deductive methods that served to the development and implementation of the survey, the inductive method is related to the study of supply and demand and in the feasibility study and sensitivity analysis were used to establish the feasibility of the project The descriptive method that allowed the description of data and population characteristics, the mathematical method allowed analysis of the different results of the application of formulas to determine the feasibility of market research, statistical method was applied to collect, organize and analyze numerical data that can be represented graphically, analytical method allowed the systematic analysis of research, decomposing parts or elements to observe the causes, nature and effects, mainly for market research. Among the conclusions, it was established that the project can be carried out, the results obtained in the analysis of supply and demand. It has been shown that there is considerable unmet demand for the product to be marketed, allowing the creation of the company. The installed capacity of the project determines that the company will be able to sell 8000 meters of carpets, which use 80% of capacity utilization for the first year. Concluding that the legal form - more convenient administrative given the nature of the company to be formed and considering the advantages of in relation to other organizations, will be formed a LIMITED LIABILITY COMPANY, and functional organizational structure levels Hierarchical as well as operating manuals, charts; which served as a guideline to implement good organization. The project reaches an investment of 68011.13, the same that will be financed with $ 33,011.13 (48.59%) by contributions from partners and $ 35,000 (51.41%) will seek financing through a credit application It may be granted by the National Finance Corporation. The financial evaluation of the project has the following results: The NPV of this project gives us a positive value of $ 68,984.18, indicating that the project is suitable to run, because the utilities that are expected during the life of the project are higher than the original investment. The time required to recover the original investment will be 2 years and 6 months approximately. The benefit / cost ratio expresses that for every dollar invested in the company will be a utility of 0.40 cents. For this project, the IRR is 35.67%, turned out higher than the opportunity cost of money. From sensitivity analysis we can see that the project is not sensitive to changes in costs. Financial indicators show that the implementation of this project is feasible. Regarding the recommendations it was established that having a positive unmet demand, it is necessary that a permanent campaign is implemented using the existing means as it says in the proposed marketing. It should seize the strategic location owned by the company to achieve market acceptance, to spread the characteristics of the company and its products sold. Buying the right equipment will enable better exploit the installed capacity of the company and use its capacity, it will not exceed 90%. Avail the loans granted by the National Financial Corporation to create business interests that are attractive to the investor